AMCCR: Adaptive Multi-QoS Cross-Layer Cooperative Routing in Ad Hoc Networks - Gawas, Mahadev A.; Gudino, Lucy J.; Anupama, K. R. (Journal of Computer Networks and Communications, 2017)
The cooperative communication technique in an ad hoc network exploits the spatial diversity gains inherent in multiuser systems and mitigates the multipath fading. This technique is necessary but perhaps not sufficient to meet the QoS demands in ad hoc network. This is due to the fact that routing protocol at the network layer is more responsible for the successful packet delivery and QoS support. In this paper, we propose an adaptive multi-QoS cross-layer cooperative routing (AMCCR) protocol that enhances the performance through the cooperation of physical, MAC, and network layers. We first formulate an approach to analyze the channel state variations for effective communication schemes at the physical layer. Secondly, we dynamically select the transmission mode to employ cooperative MAC scheme by exploiting spatial diversity. Thereafter, the network layer chooses an optimized route from source to destination through the selected best relay candidates based on multiple QoS metrics. The paper is further extended to support dual-hop half-duplex communication via selected relay by coding technique. The proposed protocol is validated by extensive simulations and compared with CD-MAC and CODE protocols. The results clearly show that the proposed cooperative cross-layer design approach significantly improves the average delay, throughput, and network lifetime of the system.